Development of naturally activated edible films with antioxidant properties prepared from red seaweed Porphyra columbina biopolymers - Cian, Raúl Esteban (2013)
The aim of this work was to study the physicochemical and antioxidant properties of phycobiliproteins-phycocolloids-based films, obtained from mixtures of two aqueous fractions extracted from Porphyra columbina red seaweed, one enriched in phycocolloids (PcF) and the other in phycobiliproteins (PF). Films with different ratios of PF:PcF (0, 25, 50, 75, 100% [w/w]) and without plasticizer addition were prepared by casting. PcF films had excellent mechanical properties (tensile strength ∼50 MPa, elongation at break ∼3% and an elastic modulus ∼17.5 MPa). The addition of PF to formulations exerted a plasticizing effect on the PcF matrix, which was manifested in moisture content, water solubility and mechanical properties of the resulting films but not in its water vapour permeability. The antioxidant capacity (TEAC) of the PcF films was significantly increased by the addition of PF and a direct relationship between TEAC and the total phenolic compounds (r2 = 0.9998) and R-phycoerythrin (r2 = 0.9942) was observed. © 2013 Elsevier Ltd. All rights reserved.